Home, Housing and Communities: Foundations for Inclusive Society - Anderson, Isobel (Social Inclusion, 2020)
This issue of Social Inclusion explores the interconnected, but multi-faceted concepts of home, housing and communities as fundamental tenets of an inclusive society. Our editorial introduces our motivation for this topic, outlines the contributions to the collection and highlights some crosscutting themes, which emerge from the articles. The research presented was largely completed in advance of the full impact of the 2020 global coronavirus pandemic. In concluding the editorial, we reflect on the equal centrality of home, housing and communities to surviving the pandemic and ensuing economic crisis and encourage greater commitment to home and housing as a human right to mitigate social and economic inequality and underpin sustainable, inclusive settlements for the future.